A portable chromium ion detection system based on a smartphone readout device. Issue 38 (2nd September 2016) - Yu, Shiting; Xiao, Wei; Fu, Qiangqiang; Wu, Ze; Yao, Cuize; Shen, Haicong; Tang, Yong
Abstract : The portable detection system based on a smartphone readout device is a potential tool for environmental monitoring. Abstract : Existing quantitative tests for detecting chromium ions (Cr) require complex instruments and trained technicians and therefore cannot be used on-site or in resource-limited areas. Herein, we designed a portable Cr(iii ) detection system based on a smartphone readout device and an Enzyme-Linked Immunosorbent Assay (ELISA). The competitive ELISA is based on a specific monoclonal antibody against Cr(iii )–EDTA and gold nanoparticles amplified the HRP signal. The readout device is comprised of a light source and a miniaturized assay platform. A smartphone with an application called "Light Meter" was used to record and process detection signals from the readout device. To demonstrate the performance, the system was used to detect Cr(iii ) in spiked water samples. The novel system had a positive correlation ( R 2 = 0.995) between the signal and Cr(iii ) concentration with a linear detection range of 0.8–50 ng mL −1 and a limit of detection of 0.81 ng mL −1 . Furthermore, the assay was used to detect Cr(iii ) in Pearl River water samples. The results obtained by this method were consistent with those obtained by ICP-MS. This test system also showed a good selectivity for the detection of Cr(iii ) compared with other heavy metals. These results from our portable detection system based on a smartphone readout device show promise in using the system for environmental monitoring.